Bakteri Endofit Penghasil AHL-Laktonase Asal Tanaman Pisang untuk Pengendalian Penyakit Darah: Endophytic Bacteria Producing AHL-Lactonase from Banana Plant to Control Blood Disease - Abidin, Anugrawati; Giyanto; Nawangsih, Abdjad Asih (Jurnal Fitopatologi Indonesia, 2025)
Endophytic Bacteria Producing AHL-Lactonase from Banana Plant to Control Blood DiseaseBlood disease is an important disease in banana that caused 100% yield loss. The Ralstonia solanacearum Phylotype IV as the causal agent for this disease express their virulence genes through quorum sensing (QS) mechanism by using acylated homoserine lactone (AHL) as autoinducer. AHL-lactonase enzyme is produced by bacteria, and its potential as biocontrol agents performed through anti-QS. This research was aimed to obtain endophytic bacteria isolates producing AHL lactonase for controling R. solanacearum in banana plants. The research stages include isolation and selection of endophytic bacteria from banana plant as producer of AHL lactonase by using bioassay and molecular, the effectiveness testing of the bacterial isolates in suppressing R. solanacearum pathogenic virulence factors, in planta testing for controlling R. solanacearum, and molecular identification of potential bacterial isolates. We successfully explored endophytic bacteria from low-, medium-, and up-land consisted several varieties of banana, resulting 152, 204, and 130 isolates, respectively. Further selection using bioindicator showed five isolates with anti quorum sensing activity against Chromobacterium violaceum. Detection of aiiA gene by polymerase chain reaction using specific primer indicated all of five isolates AHL degradation activity resulted 753 bp amplicon that has been identified as aiiA gene. These isolates (CBP1, DBT17, DBT7, DBK2, and CBN13) were able to suppress the formation of exstracellular polysacharide (EPS) produced by R. solanacearum with suppression level of 75.67%, 90.81%, 87.67%, 92.72%, 81.08%, and were able to inhibit wilt symptom in banana plant. Nucleotide sequences of aiiA gene of these five isolates has homology with aiiA genes from Bacillus cereus, B. thuringiensis, B. substilis, B. amyloliquefaciens.